Prevalence, Risk Factors, and Diagnostic Efficacy of Bovine Tuberculosis in Slaughtered Animals at the Chiang Mai Municipal Abattoir, Thailand - Singhla, Tawatchai; Boonyayatra, Sukolrat (Frontiers in Veterinary Science, 2022)
This study aimed to 1) investigate the prevalence of bovine tuberculosis (bTB) in slaughtered animals at the Chiang Mai Municipal abattoir in Chiang Mai, Thailand; 2) identify animal-level risk factors for bTB at the abattoir; and 3) evaluate the performance of techniques for bTB detection at the abattoir. From April 2020 to March 2021, 161 animals registered for slaughter were randomly selected for the study. Animal data including age, sex, species, body condition scores, and origins of the animals were collected. Meat inspection was performed by a trained meat inspector. Tissue samples of the lung, liver, and lymph nodes were collected for histopathological diagnosis and polymerase chain reaction (PCR) detection of Mycobacterium bovis. The prevalence of bTB during meat inspection and PCR was calculated separately. Animal-level factors affecting bTB were determined using multivariate logistic regression analysis. The performance of meat inspection and PCR was evaluated using a Bayesian approach. The prevalence of bTB was 12.4% (20/161) and 34.8% (56/161) when the disease was diagnosed using meat inspection and PCR, respectively. Buffaloes had a significantly higher risk of being identified as bTB-positive using PCR compared to beef cattle (odds ratio = 2.19; confidence interval = 1.11–4.30). The median of posterior estimates of sensitivity (Se) and specificity (Sp) to detect bTB using meat inspection were 20.8% (95% posterior probability interval [PPI] = 9.1–36.5%) and 87.8% (95% PPI = 79.6–95.4%), respectively. The medians of the posterior estimates of Se and Sp for PCR were 88.6% (95% PPI = 70.5–98.3%) and 94.4% (95% PPI = 84.7–98.8%), respectively. These findings demonstrate that bTB is highly prevalent among slaughtered animals. PCR can be used as an ancillary test for bTB surveillance at abattoirs in Thailand.